Antibacterial, antibiofilm and molecular modeling study of some antitumor thiazole based chalcones as a new class of DHFR inhibitors. (November 2019) - Alrohily, Waad D.; Habib, Mahmoud E.; El-Messery, Shahenda M.; Alqurshi, Abdulmalik; El-Subbagh, Hussein; Habib, El-Sayed E.
Abstract : Some synthesized antitumor derivatives of thiazole based chalcones including thiazolo[2, 3- b ]quinazoline and pyrido[4, 3- d ]thiazolo[3, 2- a ]pyrimidine analogues were subjected to be tested against standard microbial strains. Compound 18 showed higher activity against both Gram-positive and Gram-negative bacteria with MIC of 1.0, 1.0, 2.0, 2.0 and 4.0 μg/ml against S. aureus, B. subtilis, M. luteus, E. coli and P. aeuroginosa respectively which is better than ampicillin and very relative to ciprofloxacin standards. Moreover, this compound shows a good anti-biofilm activity against the Gram positive bacteria . Molecular docking studies of synthesized compounds against DHFR enzyme were carried out. Interestingly, active anticancer candidates 22, 38, 40 and 41 in addition to most active antimicrobial agents 15, 18 and 20 bind to DHFR with nearly the same amino acid residues as MTX especially mentioning Arg28, Arg70, Asn64 and Lys68 which support our hypothesis that these compounds could act as antitumor or antibacterial via DHFR inhibition. Flexible alignment and surface mapping techniques have further provided lipophilic distributions supporting effective binding to DHFR. ADMET calculations for compounds 15, 18 and 20 suggested that they could be good orally absorbed antibacterial agents while compound 38 could be an orally absorbed anticancer agent with diminished toxicity. The results highlight studied thiazole based chalcones as efficient leads for designing new future antibacterial drug candidates. Highlights: Testing antimicrobial activity of thiazolo[2, 3- b ]quinazoline and pyrido[4, 3-d]thiazolo[3, 2- a ] pyrimidine analogues. Molecular docking was used to examine binding of compounds that may act as DHFR inhibitors. Active antitumor 22, 38, 40, 41 and antimicrobial agents 15, 18 and 20 bound to DHFR as MTX . ADMET calculations proved good oral absobtion for antimicrobial and anticancer agents.